Integrating plant species contribution to mycorrhizal and seed dispersal mutualistic networks - Correia, Marta (2019)
Mutualistic interactions like those established between plants and mycorrhizal fungi or seed dispersers are key drivers of plant population dynamics and ecosystem functioning; however, these interactions have rarely been explored together. We assembled a tripartite fungi-plant-disperser network in the Gorongosa National Park-Mozambique, to test (1) if diversity and importance of plant mutualists above- and belowground are correlated, and (2) whether biotically and abiotically dispersed plants are associated with distinct arbuscular mycorrhizal fungi (AMF). We quantified seed dispersal by animals for 1 year and characterized the AMF of 26 common plant species. Sixteen plant species were dispersed by 15 animals and colonized by 48 AMF virtual taxa (VT), while the remaining 10 plant species were not dispersed by animals and associated with 34 AMF VT. We found no evidence for a correlation between the number of plant partners above- and belowground or on plant specialization on both types of partners. We also found no evidence for differentiation of AMF communities between biotically and abiotically dispersed plants. Our results suggest that the establishment of plant interactions with seed dispersers and mycorrhizal fungi is largely independent and that both biotically and abiotically dispersed plants seem to associate with similar communities of AMF.